PENGEMBANGAN BAHAN PENDAMPINGAN IMAN ANAK DENGAN METODE DINAMIKA KELOMPOK BERBASIS PERMAINAN MASA ADVEN-NATAL TAHUN LITURGI C - Rosalia Dewi Shinta; Irene Hartutik; Yustinus Joko Wahyu Yuniarto (Lumen: Jurnal Pendidikan Agama Katekese dan Pastoral, 2022)
This research includes research on the development of mentoring materials with the research subject being Child Faith Assistance (PIA) using the Research andDevelopment (RND) research and development model. Data collection was carried out on 10 validators consisting of priests, elementary school teachers, PIA and OMK assistants at the Most Holy Heart of Jesus Parish Metro. Data collection techniques used interview methods, questionnaires, validation test I, validation test II and FGD. Children's faith assistance at the Most Holy Heart of Jesus Parish Metro is held 2 times a month on Sundays. The materials used in advocating children's faith during the Advent-Christmas Period that have been used so far do not have a syllabus but have used the liturgical year C. The material for advocating children's faith in the Advent-Christmas material for the liturgical year C through the play method has been proven valid with two stages of validation with results of 3.3 and 3.5 out of a scale of 4. The PIA material for the liturgical year C with the group dynamics method developed in this study is feasible to use because it has gone through a feasibility test using the Forum Group Discussion (FGD) technique